Where Was Your Church before Luther? Claims for the Antiquity of Protestantism Examined - Barnett, S. J. (Church history, 1999)
During and after the Reformation, one of the most pressing issues for Protestants was to locate an appropriate answer to a disarmingly simple Catholic question: where was your church before Luther? Catholic propagandists hoped to undermine the legitimacy of Protestantism by contrasting its evident novelty against the relative antiquity of Roman Catholicism. Implicit in the charge of novelty was the accusation that Protestantism represented only a counterfeit religion. The Reformed religion was considered to be but an invention of iniquitous religious charlatans who—in league with monarchs and aristocrats—were exploiting religious credulity for material and sexual ends. Under cover of religion, they were advancing their own political power, plundering the wealth of the church and turning their backs upon the moral code of Christianity. Catholic apologists usually designated Luther and Calvin as Manichean heretics—from the thirdcentury dualist heresy of Manes.